STRATEGI PENGEMBANGAN AGROWISATA SEBAGAI DAYA TARIK WISATA DI DESA GENGGELANG LOMBOK UTARA - Ibnu Huzaefah; I Putu Gede; Primus Gadu (Journal Of Responsible Tourism, 2023)
This study discusses agro-tourism development strategies as a tourist attraction in Genggelang Village, Gangga District, North Lombok Regency. This type of research is a descriptive qualitative research, with the aim of describing the potential of agro-tourism in Genggelang Village, Gangga District, North Lombok Regency. The results of this study are presented using descriptive methods and SWOT analysis to obtain answers to the problem formulations, namely a description of the agro-tourism potential found in Genggelang Village, the formulation of agro-tourism development strategies in Genggelang Village. The data collection techniques used in this study were observation, interviews, questionnaires and documentation. Determination of informants is determined by purposive sampling technique. There are important findings in the research, there are several agro-tourism potentials such as coffee, cocoa, durian, and vanilla plantations. Based on research, and internal strategic factors analysis summary (IFAS), external strategic factors analysis summary (EFAS) and then SWOT analysis so that an agro-tourism development strategy for Genggelang village can be formulated, namely a rapid growth strategy. It was concluded that the appropriate agro-tourism development strategy for Genggelang Village is a rapid growth strategy and the strategy that can be implemented in the development of agro-tourism in Genggelang Village is the Strength Opportunity.